Speed sensorless field oriented control of ac induction motor using model reference adaptive system - Ismael, Ahmed Jameel (2020)
In order implement the vector control technique, the motor speed information is required. Incremental encoder, resolvers and tachogenerator, are used to reveal the speed. These sensors require careful mounting and alignment and special attention is required with electrical noises. Sensorless speed vector control is greatly used and applied in induction machine drives instead of scalar control and vector control for their robustness and reliability, and very low maintenance cost. In this project MRAS based techniques are used to estimate the rotor speed based on rotor flux estimation, the estimated speed in the MRAS algorithm is used as a feedback for the vector control system. The model reference adaptive control system is predicated on the comparison between the outputs of adjustable model and reference model. The error between them is employed to drive a suitable adaptation mechanism which generates the estimated rotor speed for the adjustable model. And indirect vector control scheme controls the flux and torque by restricting the torque and flux errors with respective hysteresis bands, and motor flux and torque are controlled by the stator voltage space vectors using optimum inverter switching table. Modeling and simulation of the induction machine and the vector control drives implemented in MATLAB/SIMULINK. Simulation results of proposed MRAS and indirect vector control technique are presented.